2019
DOI: 10.1016/j.cortex.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Naming and conceptual understanding in frontotemporal dementia

Abstract: Behavioural variant frontotemporal dementia (bvFTD) is characterised by behaviour change and impaired executive skills. There is growing evidence that naming difficulties may also be present but the basis for these is unclear. A primary semantic deficit has been proposed, although executive contributions to naming breakdown are also possible. The study aimed to improve understanding of the naming disorder in bvFTD through direct comparison with semantic dementia (SD), and examination of neural correlates. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Sixteen studies examined language impairment in bvFTD. Nine studies reported impairments in naming 49,[66][67][68][69][70][71][72] with four of these studies specifically identifying action naming as a deficit. 49,66,71,72 Other impairments included errors in word repetition, phonological errors, reduced speech output, verbal perseverations and echolalia, 69 and difficulties with organizing narratives 73 and with grammar.…”
Section: Behavioral Variant Frontotemporal Dementiamentioning
confidence: 99%
“…Sixteen studies examined language impairment in bvFTD. Nine studies reported impairments in naming 49,[66][67][68][69][70][71][72] with four of these studies specifically identifying action naming as a deficit. 49,66,71,72 Other impairments included errors in word repetition, phonological errors, reduced speech output, verbal perseverations and echolalia, 69 and difficulties with organizing narratives 73 and with grammar.…”
Section: Behavioral Variant Frontotemporal Dementiamentioning
confidence: 99%
“…These findings are consistent with previous studies which have identified different regions to be related to anomia according to the likely linguistic subdomain affecting naming ability. Whilst anterior temporal regions have been found to correlate with naming deficits when semantic impairment is present, such as in the semantic variant of PPA [ 9 , 10 , 23 ], frontal lobe regions may be involved when there is impairment of word generation and motor aspects of speech and language, such as in the non-fluent variant of PPA. These include the inferior frontal lobe, opercular and anterior insula [ 24 26 ], as was seen here in both GRN and C9orf72 mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in any of these genes can lead to impaired naming ability (anomia), MAPT mutation carriers tend to show the most pronounced deficit with previous studies showing that such difficulties can even be detected before symptom onset [ 3 5 ]. Importantly, whilst anomia is one of the key manifestations of people with the language variant of FTD [ 6 ], a similar pattern of naming deficits, albeit often less severe, has been found in the early stages of people presenting with both behavioural and motor symptoms [ 7 9 ], suggesting that impairment could potentially be seen in all of the phenotypes of genetic FTD.…”
Section: Introductionmentioning
confidence: 99%
“…After 1 y of anti-seizure medication treatment, picture-naming function improved in PWE with FLE in our study. Functional magnetic resonance imaging was used to locate the encephalic region and network connectivity responsible for naming, and temporal lobe was involved in it ( 39 , 40 ). It might be the pathological changes in the temporal lobe for PWE with TLE leading to no improvement in picture-naming function to anti-seizure medication treatment.…”
Section: Discussionmentioning
confidence: 99%